STRATEGI GERAKAN DAKWAH FRONT PEMBELA ISLAM ACEH - Said Fadhlain (SOURCE : Jurnal Ilmu Komunikasi, 2017)
This study discusses the Strategy of FPI Dakwah Movement in Aceh. The problems studied in this research are formulated in a problem formulation: How is the understanding of the mission movement of FPI in Aceh ? How is the strategy of the mission movement of the FPI in Aceh ?, What are the opportunities and challenges of the mission movement of the FPI in Aceh? This research is field research with data collection technique through interview technique and documentation study. The research method used is descriptive research method qualitative analysis, which is trying to describe the systematic facts or characteristics of a particular population or specific field in actual and accurate. The results showed, among others: Understanding propaganda movement according to FPI in Aceh, namely amar makruf nahi munkar. FPI is an Islamic organization that  Ahlussunnah Waljama'ah (Aswaja) faith who using Imam Syafi'i mazhab and aqidah Asy'ariyah Maturidiyah, and based on bilhikmah, mau'idatul hasanah and mujadalah. Strategy of mission of FPI in Aceh, in addition to seeking new followers, Rely on recruitment of members who come from pengajian participants, jama'ah mosque, or students in boarding schools run by FPI leaders. The mission of FPI by way of hisbah, the demonstration and sweeping of the eradication of immoral place, the dakwah of billisan, bilqalam and bilhal The opportunity of FPI preaching in Aceh has been well known by the community, especially the dayah ulama who give full support to FPI, even some heads of regions Preaching of FPI in Aceh. While the main challenge of FPI preaching in Aceh is the role of mainstream media that tends to exploit the negative side of the reporting of FPI Aceh's activities, the weakness of government and police efforts to enforce the law against the violation of Islamic Sharia in Aceh, as well as the violent FPI dakwah. Keywords: Strategize, Movement, Dakwah, and Front Pembela Islam (Islamic Defenders Front)